Causes and Trends of Motorcycle Accidents (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Road safety has long been considered as one ofthe social responsibilities to the Malaysian Government. Inthe visibility of this responsibilities, multiple bodies concernon road safety has been formed within the governmentdepartments, private agencies, and voluntary organizations.The current study was carried out to understand the recenttrend and statistics of road motorcycles in Kajang,Malaysia. The statistics for road accidents and the relatedcasualties in Malaysia from 2005 to 2008 was obtained fromthe Bukit Aman Police Headquarters. The statistics ofregistered motor vehicles in Malaysia will be provided byRoad Transport Department of Malaysia. Data will beanalyzed using SPSS software. Descriptive and hypothesistesting techniques were used to obtain the results based onthe stated objectives of the study. From the crash statistics,it can be revealed that Kajang has a relatively higherincidence of casualties (dead, seriously injured and lightlyinjured). In addition, the results show that the young ridersof motorcycles among the age of 16 to 20 years from themajority of those who die in motorcycles accidents.Moreover, it is recognized that the considerable percentageof the motorcyclists and the pillion riders did not wearsafety helmets when they were traveling on the roadsnetwork. The Malaysian government has to organize manymotorcycle safety campaigns in the coming few years.